Safety of Early Discharge After Primary Angioplasty - Salman, Ahmad; Akhtar, Muhammad Hammad; Riaz, Rehan; Ali, Liaqat; Abbas, Shahid; Saeed, Muhammad Hamid (Biological and Clinical Sciences Research Journal, 2025)
Early discharge following primary percutaneous coronary intervention (PPCI) for ST-elevation myocardial infarction (STEMI) has gained attention due to its potential to optimize healthcare resources without compromising patient safety. While evidence from high-income countries supports this practice in carefully selected low-risk patients, data from low- and middle-income countries, including Pakistan, remain limited. Objective: To assess the safety and outcomes of early discharge (≤48 hours) compared with delayed discharge (>48 hours) after PPCI in STEMI patients. Methods: This prospective observational cohort study was conducted at Faisalabad Institute of Cardiology, Pakistan, from January to December 2024. A total of 100 consecutive STEMI patients undergoing successful PPCI were enrolled and stratified into two groups: early discharge (n = 50) and delayed discharge (n = 50). Discharge criteria included hemodynamic stability, absence of recurrent ischemia, stable rhythm, and adequate renal function. The primary outcome was all-cause mortality at 7, 30, 90, and 120 days. Secondary outcomes included unplanned readmission, reinfarction, stent thrombosis, stroke, repeat revascularization, major bleeding, and major adverse cardiac events (MACE). Statistical analyses included t-tests, chi-square tests, Fisher’s exact tests, and logistic regression. Results: The mean age was 56.8 ± 10.4 years, with 74% males. Baseline demographics and risk factors were similar between groups. Mortality at 120 days was 4.0% in the early discharge group versus 6.0% in the delayed group (p=0.64). No significant differences were observed in readmission (4.0% vs. 6.0%, p=0.64), reinfarction (2.0% vs. 4.0%, p=0.56), stent thrombosis (0% vs. 2.0%, p=0.31), stroke (0% vs. 2.0%, p=0.31), repeat revascularization (2.0% vs. 4.0%, p=0.56), or major bleeding (2.0% vs. 4.0%, p=0.56). MACE occurred in 6.0% of early discharge and 12.0% of delayed discharge patients (p=0.29). Event-free survival at 120 days was 94.0% and 88.0%, respectively (p = 0.29). Conclusion: Early discharge (≤48 hours) after PPCI in selected low-risk STEMI patients demonstrated comparable mortality and adverse event rates to delayed discharge, supporting its safety in the Pakistani healthcare context. This strategy could improve hospital resource utilization without compromising patient outcomes.